Relationship between arterial hypertension and central obesity in mothers - Araujo-Contreras, Jesús María (Universidad Autónoma de Tamaulipas, 2015)
Arterial hypertension (AHT) is associated with other diseases, primarily obesity. Its high prevalence represents a serious health problem in the world. The objective of the study was to determine the relationship between arterial hypertension and central obesity in mothers of three urban areas of the city of Durango, Mexico. In order to accomplish this goal, a cross-sectional study was conducted through a printed validated survey, which included 806 participants. Information about their socio-demographic characteristics and background of hypertensive disease was obtained. Measurements of blood pressure, circumference of waist and hip were performed. The analysis included descriptive statistics, tests of independence and epidemiological risk measurement. The participants had age mean of 41.4 years and 9 years of completed schooling. 59.8 % were married, 69.3 % housewives and 87.8 % affiliated with any health institution. The reported prevalence of hypertension was of 20.3 %; in 50.6 % of the total population family history of the disease was present. Elevated blood pressure obtained by direct measurement was 19.7 %. Systolic hypertension was found in 8.4 % and diastolic in 17.3 %. Abdominal obesity was evident in 82.9 %; the risk of developing AHT was 3.1 times higher in mothers with abdominal obesity. Family history of hypertension and central obesity, one of the main cardiovascular risk factors, increased the risk for developing hypertensive disease. Archive XML (SciELO)